Perlawanan Masyarakat Hindu Bali Terhadap Reklamasi di Denpasar 1990-2014 - Buhan, Ris; Bagus Wirawan, Anak Agung; *, Sulandjari (Humanis; Vol 19 No 1 (2017))
Denpasar City is one of the tourist destinations in the province of Bali. The rapid development of tourism in the city of Denpasar making development policy goes so fast in the 90s. Development is so fast to make the appearance of the symbols of modernity, namely the reclamation and the reclamation Serangan Padanggalak Beach. But the government's development policies are not in line with the aspirations of the Hindu society Denpasar which makes their resistance against the reclamation. Factors that cause people to fight against the background by a variety of factors. These factors, among others, social factors, economic factors of society, environmental factors, cultural factors, and factors of policy set by the government of Denpasar. Resistance to the symbols of modernity implications to the public, governments, and investors. Implications arising covering various aspects ranging from social, economic, cultural, and environmental.
Keywords: modernity, reclamation, Serangan